KINETICS OF SARS-CoV-2 NEUTRALIZNG ANTIBODIES AFTER TWO DOSES OF BNT162b2, (BioNTech/Pfizer) Vaccine - Tosheska-Trajkovska, Katerina; Emin, Melda; Ampova, Hristina; Petrushevska-Stanojevska, Elena; Kostovska, Irena; Bogdanska, Jasna; Brezovska, Julijana; Topuzovska, Sonja (Journal of Morphological Sciences, 2021)
The neutralizing antibody is an antibody that can block the binding and infection process of the virus cell receptor. MAGLUMI Â® Neutralizing Antibody kit could detect all those antibodies that can block RBD-ACE2 combination. Studies evaluating the long-term duration of neutralizing antibodies (NAbs) after SARS-CoV-2 vaccination are important to develop vaccination strategies. In this study, 131 healthcare workers (HCW) received the two-dose BNT162b2 regimen. Of the 131 HCW enrolled in the study, 85 (64.9%) were female and 46 (35.1%) were male, with a mean age (Â±SD) of 45.2 Â± 10.31 (range 26-55) years. Of them, 91 were seronegative and 40 were seropositive at baseline. The samples were collected at different time points. Neutralizing antibodies (NAbs) were measured by CLIA method using Maglumi 800 analyzer. The median days that neutralizing antibodies were positive were 96 and 201 days for rapid and slow attenuation, respectively. No age and gender difference were found in Nabs levels. The decline in NAbs was pronounced (-96.8%) and approximately 47% of those tested were negative at day 180. Whether this decline correlates with a corresponding decline in clinical efficacy against the virus would need to be investigated in appropriate clinical trials.  BNT162b2 elicits strong NAb production, especially 28 days after initial inoculation. Further investigations are urgently needed to improve both the comparability of data and our understanding of which levels should be considered predictive of immune protection. Keywords:  Covid -19,  SARS-CoV-2, mRNA vaccine, BNT 162b2, antibody response.   https://doi.org/10.55302/JMS2143198tt